2019
DOI: 10.3390/cells8080834
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Involvement in the Adaptive Response to Chronic Exposure to Environmental Pollutants and High-Fat Feeding in a Rat Liver and Testis

Abstract: In our modern society, exposure to stressful environmental stimuli, such as pollutants and/or chronic high-fat feeding, continuously induce tissular/organ metabolic adaptation to promote cellular survival. In extreme conditions, cellular death and tissular/organ damage occur. Mitochondria, as a cellular energy source, seem to play an important role in facing cellular stress induced by these environmental stimuli. On the other hand, mitochondrial dysfunction and oxidative stress play a key role in environmental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 126 publications
1
12
0
Order By: Relevance
“…Recently, histological and molecular analysis indicated that oral exposure to a moderately low dose of DDE (10 mg/kg bw) for 4 weeks was able to elicit morphological alterations, cellular oxidative stress, and lipid peroxidation in rat tissues [47,48,56,58]. Studies also evidenced the presence of similar morphological and oxidative damage caused by the fat diet alone [47,48,56,58]. In the liver, an HF diet induced steatosis of hepatocytes, and DDE treatment-tissue inflammation and cellular vacuolization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, histological and molecular analysis indicated that oral exposure to a moderately low dose of DDE (10 mg/kg bw) for 4 weeks was able to elicit morphological alterations, cellular oxidative stress, and lipid peroxidation in rat tissues [47,48,56,58]. Studies also evidenced the presence of similar morphological and oxidative damage caused by the fat diet alone [47,48,56,58]. In the liver, an HF diet induced steatosis of hepatocytes, and DDE treatment-tissue inflammation and cellular vacuolization.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that the presence of DDT and its metabolites in animal tissues causes oxidative stress and mitochondrial damage [43][44][45][46][47][48], whereas few data, often controversial, are available on the effects of these substances on MT expression and synthesis. A study performed by Ben Miled and coworkers [49] showed an increase in MT content in hepatocytes of rats receiving a single intraperitoneal injection of 100 mg DDT/kg body weight (bw).…”
Section: Metallothioneins and Ddt Metabolitesmentioning
confidence: 99%
“…For example, oxidative stress generated by exposure to the insecticide permethrin is linked to the detoxifying activities of CYP450 enzymes, and other enzymes involved in oxidation and hydrolysis processes [ 364 ]. Organochlorine compounds such as DDT lead to an increased ROS production through activation of CYP450 gene expression involved in its detoxifying pathway in exposed rat liver [ 211 ]. The biotransformation reactions of organophosphorus compounds, during which an excess of free radicals is generated, also produces ROS [ 187 ].…”
Section: Oxidative Stress In Nafld: Role Of Pesticidesmentioning
confidence: 99%
“…In fact, various chemical families of insecticides seem to be involved, i.e., organochlorine, pyrethroid, neonicotinoid, and organophosphorus compounds ( Table 2 [ 148 , 184 , 185 , 195 , 196 , 197 , 198 , 199 , 200 , 201 , 202 , 203 , 204 , 205 , 206 , 207 , 208 , 209 , 210 ]). Moreover, HFD components may act as a vehicle for pesticides, allowing them to reach target organs more easily, as proposed in [ 136 , 211 ]. This finding suggests that a different bioavailability of pesticides in mice fed with an HFD versus normal chow diet may explain, at least in part, dissimilar outcomes with pesticide exposure in different studies.…”
Section: Introductionmentioning
confidence: 99%
“…However, at 13 weeks of age (Figure 4(G)) thermally conditioned rabbit in both breeds had overexpressed hepatic UCP2 compared to their control groups indicating a protective function of this overexpression and improve thermotolerance acquisition resulted from thermal conditioning at early life. The substantial role of UCP2 is to monitor mitochondria-derived ROS production (Sreedhar and Zhao 2017) and the upregulation of UCP2 may reduce ROS production due to its antioxidative protective effects (Huang et al 2019;Migliaccio et al 2019). Besides, UCP2 overexpression may enhance cytoprotection by alleviating oxidative stress (Mattiasson et al 2003) and attenuating superoxide production to protect hepatic damage in mice due to oxidative stress (Zhang et al 2003).…”
Section: Contrasting Responses Of Nzw and Bb Rabbits Due To Thermal Conditioning At 42 Day Of Agementioning
confidence: 99%